DEVELOPMENT OF A NUMERACY LITERACY BASED MATHEMATICS TEST ASSESSMENT ON INTEGERS IN PRIMARY SCHOOLS - Mohammad Yusuf Randy; Sukoriyanto Sukoriyanto; Sri Rahayuningsih; Radeni Sukma Indra Dewi; Shirly Rizki Kusumaningrum (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
One of the mathematics materials students considers difficult is integer material. This affects the results of AKM Numeracy, which is not optimal, especially in the number domain. This study aimed to develop a numeracy literacy-based mathematics test instrument on whole number material in grade V elementary school. This type of research is Research & Development with the development stages of the Thiagarajan 4D model (defining, designing, developing, and disseminating). The instruments developed include question grids as guidelines for making questions, questions and answer keys to test students' numeracy skills and scoring guidelines as a tool for giving student scores. The number of questions developed was three multiple-choice questions and seven complex multiple-choice questions. The principal and fifth-grade teacher validated this test instrument and obtained very valid results. The instrument was tested on fifth-grade students of SDN Kasembon 3 in the 2023/2024 school year and received the results of the item validity test getting a valid level on each item, the reliability test getting a high level, the differentiator test getting a sufficient and reasonable level, and the difficulty test getting an easy and moderate level. So, this numeracy literacy-based mathematics test instrument on integer material is feasible and can measure numeracy skills very well